Implementing Open Innovation: The Case of Natura, IBM and Siemens - Cely Ades; Aline Figlioli; Roberto Sbragia; Geciane Porto; Guilherme Ary Plonski; Kleber Celadon (Journal of Technology Management & Innovation, 2013)
This paper analyses three case firms whose innovation management processes have been consolidated. The companies Natura, IBM (Brazilian Subsidiary) and Siemens (ChemTech/Brazil) were studied with the purpose of analysing the implementation of OI, particularly in terms of: (a) its alignment with existing corporate strategy; (b) its requirements such as culture, skill and motivation; (c) the strategy and the implementation process; (d) the results achieved (e) the present barriers and enablers. The research is qualitative in nature and employs a descriptive approach. The main results of this study, obtained using a method called ‘Collective Subject Speech’ , show that the implementation of OI, both structured and non-structured, is mainly challenged by cultural issues. It has been observed that the implementation of OI process is at its embryonic stage in all case firms and that this occurs along with investments in closed innovation, meaning that OI results cannot be explored at this stage of the implementation, as there is a long way to consolidate these practices in the case firms studied.